SOIL DILUTION METHOD FOR THE ESTIMATION THE INOCULUM POTENTIAL OF Plasmodiophora brassicae - HASSE, Ionete; MAY DE MIO, Louise Larissa; LIMA NETO, Vismar da Costa (Scientia Agraria, 2007)
The producers of brassicas in the Metropolitan region of Curitiba-PR have identified severe damage in their crops due to the disease club root caused by P. brassicae. In that region, there is lack of data concerning the degree of soil infestation. Therefore, the objective of this paper was to design a comparative methodology to quantify the risk of infection of the disease in two soils contaminated from two areas in Colombo-PR, (Boicininga and Serrinha). The experiment was conducted under greenhouse conditions using ruccula (Eruca sativa Mill) as the host plant: it was sowed in pots with infested soil and diluted (mixed with sterile soil) in the following proportions: 1:1, 1:2, 1:4, 1:8, 1:16, 1:32. Forty-five days after planting, aerial fresh matter, incidence and disease severity were determined. The soil in Boicininga presented disease severity up to 1:32 dilution, whereas the soil in Serrinha presented a decrease in disease severity from 1:4 dilutions onwards. There was no significant difference at 5% level between the treatments for the incidence and severity in dilutions with Boicininga soil. From Serrinha soil the plants presented a decrease in the variables incidence and severity. The dilution method was revealed as an important tool in the assessment of the potential of development of the disease, and can be recommended to distinguish inoculum potential of P. brassicae in crucifer’s productions fields.